Laryngeal sensory dysfunction in laryngeal hypersensitivity syndrome. Issue 6 (25th July 2013) - Vertigan, Anne E.; Bone, Sarah L.; Gibson, Peter G.
Abstract: Background and objective: Diseases associated with laryngeal dysfunction include chronic refractory cough (CRC), paradoxical vocal fold movement (PVFM), muscle tension dysphonia (MTD) and globus pharyngeus. We hypothesized the presence of a common sensory laryngeal dysfunction, the 'laryngeal hypersensitivity' syndrome, in these conditions. The aim of the study was to compare symptoms and sensory function in patients with CRC, PVFM, MTD and globus. Methods: The 103 participants included healthy controls ( n  = 13) and four case groups: CRC ( n  = 33), PVFM ( n  = 28), globus pharyngeus ( n  = 11) and MTD ( n  = 18). Participants completed self‐report questionnaires: Symptom Frequency and Severity Scale, Voice Handicap Index and the Laryngeal Paraesthesia Questionnaire; and quantitative sensory testing: capsaicin cough reflex sensitivity, hypertonic saline challenge, the timed swallow test, acoustic voice testing, cough frequency monitor and a voice stress test. Results: All case groups reported a high‐symptom burden in comparison to controls. The case groups showed a similar pattern of symptoms, with impairment in each of the cough, respiration, vocal and upper airway symptom domains. Objective testing revealed significant sensory impairment in the case groups compared to controls and also showed an overlap in sensory dysfunction between the four case groups. Furthermore, there was cross‐sensory stimulation of symptoms whereby stimulation of a particular response resulted in symptoms in another domain. Conclusions: These discrete clinical laryngeal syndromes display considerable overlap in their clinical features and a common sensory dysfunction, supporting the 'laryngeal hypersensitivity' hypothesis. Reconceptualizing functional laryngeal disorders as a form of laryngeal hypersensitivity syndrome provides an alternative approach to management of these perplexing conditions. Abstract : Laryngeal sensory function is impaired in patients with chronic cough, paradoxical vocal fold movement, globus pharyngeus and muscle tension dysphonia. This study is the first to quantify sensory dysfunction and identify the extent of overlap between the conditions. It provides a hypothesis for development of further treatments for these conditions. See Editorial, page 893